2017
DOI: 10.1515/jef-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Athletes: Sensory Dimensions of Recreational Endurance Sports

Abstract: Sport has become increasingly popular with recreational athletes over the last couple of decades. This has only gained minimal attention so far from scholars interested in the relations between recreational sports and everyday culture. With this paper, we seek to contribute to this field by scrutinising the sensory dimensions of recreational sport. Rather than probing into or highlighting isolated senses, we look at sensory dimensions understood as a combination of different, non-separable sensory experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The discussions of confidence in this paper not only address a lack of understanding in relation to participants’ SfD experiences, but they also provide support for Tamminen and Bennett’s (2017) call for greater sociological inquiry into emotions within sporting contexts. The intersubjective, embodied, and situated nature of emotions are readily apparent within the world of sport at all levels, and the engagement of the body in such activities can heighten the sensorial experiences of individuals (Allen-Collinson and Owton, 2015; Groth and Krahn, 2017). Such vivid data are being overlooked to a large degree within sport and exercise research, despite the potential to access such personal accounts of an individual’s lived body (Merleau-Ponty, 1968), dys-appearing body (Leder, 1990), or intercorporeality (Csordas, 2008) during physical activity, as was the case in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discussions of confidence in this paper not only address a lack of understanding in relation to participants’ SfD experiences, but they also provide support for Tamminen and Bennett’s (2017) call for greater sociological inquiry into emotions within sporting contexts. The intersubjective, embodied, and situated nature of emotions are readily apparent within the world of sport at all levels, and the engagement of the body in such activities can heighten the sensorial experiences of individuals (Allen-Collinson and Owton, 2015; Groth and Krahn, 2017). Such vivid data are being overlooked to a large degree within sport and exercise research, despite the potential to access such personal accounts of an individual’s lived body (Merleau-Ponty, 1968), dys-appearing body (Leder, 1990), or intercorporeality (Csordas, 2008) during physical activity, as was the case in this study.…”
Section: Resultsmentioning
confidence: 99%
“…They found that despite the dominance of the psychological tradition, which tends to position emotions as being individually appraised and expressed, there is a growing corpus of sociologically-informed inquiry which instead positions emotions as intersubjective, situated, and embodied within sporting contexts. Emotion research in sport might be positioned within the growing movement towards ‘sensory’ research within sport (see Allen-Collinson and Owton, 2015), which explicitly positions the individual’s body as not only a site of physical activity, but also as a means of perception during bodily experiences (Groth and Krahn, 2017). The sensorial qualities of sport, exercise, and physical activity are intertwined with emotion and our perception of how we use our body; the excitement (or sometimes dread) of pulling on exercise clothes before an activity, the sensations of exertion (and sometimes exhaustion) through different stages of a training session, the self-identification of our physical form and the control (or lack thereof) we feel in using our limbs and body.…”
Section: Emotions In Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…For weather is lived and experienced both corporeally and cognitively, in specific contexts. We also contribute to a relatively small corpus of research on recreational endurance athletes (Groth and Krahn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In so doing, we address key contemporary sociological concerns about embodiment and somatic learning, and highlight how weather work and weather learning provide salient examples of the phenomenological conceptualisation of the mind–body–world nexus in action, for weather is lived and experienced both corporeally and cognitively, in specific contexts. We also contribute to a relatively small corpus of research on recreational endurance athletes (Groth and Krahn, 2017).…”
Section: Introductionmentioning
confidence: 99%